IMPLEMENTASI PEMBELAJARAN ENTREPRENEURIAL DALAM PENDIDIKAN SENI RUPA - Moeljadi Pranata (Fakultas Sastra Universitas Negeri Malang, 2017)
Abstract: This study aims to produce a model of entrepreneurial learning in the field of art education in secondary schools. For this purpose teachers have developed textbooks; the books are designed in accordance with entrepreneurial learning cycle. The study found that art education teaching materials have been designed according to the specific learning strategies potential to improve the entrepreneurial mindset of learners. The results of this study has offered a strategic value to develop entrepreneurship education in Indonesia, especially when considering that the results of this research offers the potential to be extended to other fields and subjects in terms of types and levela of education.Permalink/DOI: dx.doi.org/10.17977/um015v45i22017p221